2020
DOI: 10.21037/qims-19-818
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative assessment of carotid artery atherosclerosis by three-dimensional magnetic resonance and two-dimensional ultrasound imaging: a comparison study

Abstract: Background: It has been proven that magnetic resonance (MR) and ultrasound imaging are useful tools in the quantification of carotid atherosclerotic plaques. However, there are only a few pieces of evidence to illustrate the links of quantitative measurements of carotid plaques between MR and ultrasound imaging.This study looked to compare the quantitative measurements of carotid plaques and investigate their relationship between three-dimensional (3D) MR vessel wall imaging and two-dimensional (2D) ultrasound… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…Three‐dimensional ultrasound (3D‐US) is a new technique developed in recent years and has attracted much attention by presenting the three‐dimensional stereostructure of the target. Three‐dimensional ultrasound presents an objective three‐dimensional image of the target, which has advantages such as intuitiveness and reproducibility 21 . The current state‐of‐the‐art 3D‐US scanning technology is automated single scan, which obtains three‐dimensional images by a single scan to target the most realistic three‐dimensional morphological display, overcoming the early shortcomings of poor reproducibility of 3D‐US images.…”
Section: Imaging Diagnosis Of Carotid Vulnerable Plaquesmentioning
confidence: 99%
See 1 more Smart Citation
“…Three‐dimensional ultrasound (3D‐US) is a new technique developed in recent years and has attracted much attention by presenting the three‐dimensional stereostructure of the target. Three‐dimensional ultrasound presents an objective three‐dimensional image of the target, which has advantages such as intuitiveness and reproducibility 21 . The current state‐of‐the‐art 3D‐US scanning technology is automated single scan, which obtains three‐dimensional images by a single scan to target the most realistic three‐dimensional morphological display, overcoming the early shortcomings of poor reproducibility of 3D‐US images.…”
Section: Imaging Diagnosis Of Carotid Vulnerable Plaquesmentioning
confidence: 99%
“…Threedimensional ultrasound presents an objective three-dimensional image of the target, which has advantages such as intuitiveness and reproducibility. 21 The current state-of-the-art 3D-US scanning technology is automated single scan, which obtains three-dimensional images by a single scan to target the most realistic three-dimensional morphological display, overcoming the early shortcomings of poor reproducibility of 3D-US images. In addition, single scan techniques automatically slice at 1.0 mm intervals to measure volume, and plaque volumes measured by this method are more accurate than 2D-US.…”
mentioning
confidence: 99%
“…In clinical settings, ultrasound imaging is a widely used screening tool for both carotid and femoral artery plaques. A recent comparison study between ultrasound and vessel wall MRI showed that moderate to strong correlations can be found in maximum wall thickness, plaque area, and plaque length between 3D vessel wall MRI and ultrasound imaging (28). Although ultrasound imaging has limitations in characterizing the vulnerability of atherosclerotic plaques, particularly plaque compositional feature of intraplaque hemorrhage, this imaging modality can well detect lipid-rich plaques according to the presence of echolucent components (29).…”
Section: Discussionmentioning
confidence: 99%
“…In carotid MR there is extensive literature describing plaque composition and imaging techniques, but the minimum criteria for plaque size are utterly vague. In practice, criteria used in ultrasonography are frequently used in carotid MRI (26). The author's own experience, based on MR imaging of patients with advanced atherosclerosis, is that plaques are difficult to delineate because the atherosclerotic changes usually affect the entire arterial wall stretching over centimetre-long segments, not in the form of protruding plaques with clearly delineated start-and end points.…”
Section: Carotid Plaquesmentioning
confidence: 99%